Allograft Reconstruction for Extensor Mechanism Injuries - Karas, Vasili; Sherman, Seth; Hussey, Kristen; Baker, Champ, III; Bach, Bernard, Jr.; Cole, Brian; Bush-Joseph, Charles (The Journal of Knee Surgery, 2014)
Previous case reports have documented the successful use of allograft for extensor mechanism reconstruction. We hypothesized that extensor mechanism reconstruction with allograft would restore extensor power and allow patients to return to a relatively high activity level. Between 2000 and 2007, 17 patients (18 knees) underwent extensor mechanism reconstruction with either nonirradiated Achilles or whole bone-patellar tendon-bone allograft at our institution. Two patients were lost to follow-up and one underwent a total knee arthroplasty and was considered a failure. The remaining 14 patients (15 knees) returned for clinical and radiographic evaluation at a minimum 24 months postoperatively. Patients completed questionnaires using the International Knee Documentation Committee (IKDC), Tegner, Lysholm, Knee Injury Osteoarthritis Outcome Score (KOOS), Noyes sports activity, and Short Form-12 (SF-12) scoring systems. Fourteen patients with an average age at surgery of 46.48 years (range, 18–70) returned for evaluation at a median follow-up of 52 months (range, 31–98 months). Twelve of the 14 patients underwent previous surgery before allograft reconstruction. Postoperatively, the median IKDC score was 74 (range, 28–90), Tegner 8 (range, 0.5–10), Lysholm 62 (range, 28–100), KOOS pain 92 (range, 36–100), KOOS symptom 64 (range, 21–100), KOOS ADL 82 (range, 51–100), KOOS sport 50 (range, 5–95), KOOS QOL 44 (range, 12.5–100), Noyes 90 (range, 5–100), SF-12 physical 43 (range, 29–47), and SF-12 mental 49 (range, 28–64). All patients were able to perform a straight leg raise postoperatively. Five patients had an extensor lag at final evaluation averaging 8 degrees (range, 3–18). Thigh girth differential between the surgical and contralateral leg was 1.3 cm diameter. There were no postoperative infections or reruptures. Two patients required additional procedures. We believe extensor mechanism reconstruction with allograft is an effective salvage procedure in this challenging patient population.
Keywords: allograft; extensor mechanism reconstruction; patellar tendon; quadriceps tendon